Adaptive laboratory evolution of Escherichia coli K-12 MG1655 for growth at high hydrostatic pressure - Marietou, Angeliki; Nguyen, Alice T. T.; Allen, Eric E.; Bartlett, Douglas H. (Frontiers in Microbiology, 2015)
Much of microbial life on Earth grows and reproduces under the elevated hydrostatic pressure conditions that exist in deep-ocean and deep-subsurface environments. In this study adaptive laboratory evolution (ALE) experiments were conducted to investigate the possible modification of the piezosensitive Escherichia coli for improved growth at high pressure. After approximately 500 generations of selection, a strain was isolated that acquired the ability to grow at pressure non-permissive for the parental strain. Remarkably, this strain displayed growth properties and changes in the proportion and regulation of unsaturated fatty acids that indicated the acquisition of multiple piezotolerant properties. These changes developed concomitantly with a change in the gene encoding the acyl carrier protein, which is required for fatty acid synthesis.